Some reproductive characters of Himantura walga (Müller , 1841) male, in Iraqi marine waters - Al-Zaidy, Faleh; AL-Lami, Genan (Iraqi Journal of Aquaculture, 2021)
Some reproductive characters of Himantura walga (Müller, 1841) male were studied. The fish were caught from the Iraqi marine waters in the northwest of the Arabian Gulf during the period from January to December 2017. Samples were obtained by fishing boats in the Iraqi marine waters, and 102 males were collected by trawls. The gonadal somatic index was studied in males and were highest in May and September (10.048 , 9.97) respectively, and it decreased in the months February, July, and August (0.452 , 0.654, and 0.664) respectively, the results showed that there were four groups of disk width, the male clasper was also dissected as well as the canal or siphon. The appearance of matures males was observed in May and September, indicating the existence of breeding periods for the studied fish. The relationship between body weight and the disc width of the fish were estimated by formula: T W= 0.00031× (DW) 2.595 as well as the length of the clasper and the disk width of the studied fish.